Effects of dietary pH on growth performance and feed utilization of nile tilapia (Oreochromis niloticus) - Fabay, Ryan V. (Iloilo University of the Philippines Visayas, 2020)
Two feeding trials were conducted to investigate the effects of dietary pH (pH 2.5, 3.7, 4.6, 5.7-control, pH 7.0, and pH 8.0) and dietary acid source (acetic acid, citric acid, hydrochloric acid and control-no acid) on growth rate and feed utilization effficiency of the Nile tilapia fry. In addition, attractability indices of the diets at different pH and dietary acid sources were determned. Results of the first feeding trial showed that the feed with pH adusted 4.6 resulted in increased growth rate and improved feed utilization efficiency in the Nile tilapia. In the second feeding trial, the use of either hydrochloric, citric or acetic acid in adjusting the pH to the optimal 4.6 did not affect the growth performance of the fish. This study demonstrated that pH and not actually the kind of acid diet promoted growth and efficiecny in the Nile tilapia fry. Furthermore, this study provides new information on the use of acid in aquaculture as feed additive for tilapia fry, which can be added to fish feed literature.
Thesis - M. S. (Aquaculture) - Institute of Aquaculture, College of Fisheries and Ocen Sciences, University of the Philippines Visayas.
Keywords: Nile tilapia fry; Oreochromis niloticus; Feed acidity